Enabled negatively regulates diaphanous-driven actin dynamics in vitro and in vivo. - Bilancia, C.G.; Winkelman, J.D.; Tsygankov, D.; Nowotarski, S.H.; Sees, J.A.; Comber, K.; Evans, I.; Lakhani, V.; Wood, W.; Elston, T.C.; Kovar, D.R.; Peifer, M. (Developmental Cell, 2014)
Actin regulators facilitate cell migration by controlling cell protrusion architecture and dynamics. As the behavior of individual actin regulators becomes clear, we must address why cells require multiple regulators with similar functions and how they cooperate to create diverse protrusions. We characterized Diaphanous (Dia) and Enabled (Ena) as a model, using complementary approaches: cell culture, biophysical analysis, and Drosophila morphogenesis. We found that Dia and Ena have distinct biochemical properties that contribute to the different protrusion morphologies each induces. Dia is a more processive, faster elongator, paralleling the long, stable filopodia it induces in vivo, while Ena promotes filopodia with more dynamic changes in number, length, and lifetime. Acting together, Ena and Dia induce protrusions distinct from those induced by either alone, with Ena reducing Dia-driven protrusion length and number. Consistent with this, EnaEVH1 binds Dia directly and inhibits DiaFH1FH2-mediated nucleation in vitro. Finally, Ena rescues hemocyte migration defects caused by activated Dia.